Digital Personal Branding Prabowo-Gibran Melalui Facebook pada Pilpres 2024 - Anggita, Della; Asih, Situ; Shadikah, Arina Afiyati (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The 2024 Presidential Election will not only be limited to conventional campaigns such as rallies or door-to-door visits. But it has shifted to a wider and more dynamic virtual space, for example the use of the Facebook platform. Politicians who use Facebook as a medium for building their self-image or personal branding are Prabowo Subianto and Gibran Rakabuming Raka who are campaigning for the 2024 presidential election. Both of them have challenges in creating and building personal branding on digital media because of their large age difference. The purpose of this research is to determine the personal branding strategy used through the Facebook platform. A qualitative descriptive approach with multimodality analysis is the method used. The results of the research show that Prabowo-Gibran built a strong personal brand through a combination of creative content, consistent use of colors and structured message delivery. The uniqueness of Prabowo-Gibran's strategy lies in the combination of formal leadership with a personal approach that is close to the community, as well as the use of social media formats that are relevant to various audience segments. This research provides insight into the effectiveness of the use of social media in the formation of contemporary political personal branding.